(untitled) (Journal of actual problems of jurisprudence, 2019)
The article deals with the theoretical issues of implementation of judicial review in civil proceedings. Particular attention is paid to the specifi cs of the implementation process of the judiciary in civil matters and its most important elements. Keywords: judicial power, civil process, court proceedings